Four cytotoxic annonaceous acetogenins from the seeds of Annona squamosa. Issue 11 (2nd June 2016) - Miao, Y.; Xu, X.; Yuan, F.; Shi, Y.; Chen, Y.; Chen, J.; Li, X.
Abstract : Four new annonaceous acetogenins (ACGs), squamocin-I (1 ), II (2 ) and III (3 ) and squamoxinone-D (4 ), together with seven known ACGs (5 –11 ), were isolated from the seeds of Annona squamosa . The structures of all isolates were elucidated and characterised by spectral and chemical methods. Compounds1 –4 were evaluated for their cytotoxicities against Hep G2, SMMC 7721, BEL 7402, BGC 803 and H460 human cancer cell lines. Compound1 exhibited better potent activity than the positive compound and compound3 shows selectively cytotoxical activity against H460 with IC50 values of 0.0492 μg/ml. Abstract :